Neoadjuvant Hormonal Therapy is Associated with Comparable Outcomes to Neoadjuvant Chemotherapy in Post-Menopausal Women with Estrogen Receptor-Positive Breast Cancer - Marcus, David M.; Switchenko, Jeffrey M.; Prabhu, Roshan; O'Regan, Ruth; Zelnak, Amelia; Fasola, Carolina; Mister, Donna; Torres, Mylin A. (Frontiers in Oncology, 2013)
Objectives: We compared outcomes in post-menopausal estrogen receptor-positive (ER+) breast cancer patients treated with neoadjuvant hormonal therapy (NAHT) or neoadjuvant chemotherapy (NACT). Methods: We retrospectively identified post-menopausal women who received either NAHT or NACT for non-metastatic, non-inflammatory, ER+, Her2neu negative breast cancer from 2004 to 2011. We compared long-term rates of locoregional relapse free survival (LRFS), distant metastasis free survival (DMFS), and overall survival (OS) using the Kaplan–Meier method. The Cox proportional hazards model was used to identify patient and disease factors significantly associated with these endpoints. Results: We identified 99 patients in our study, including 27 who received NAHT and 72 who received NACT. There were no differences in 4-year LRFS, DMFS, or OS between groups. On Cox proportional hazards modeling, the type of systemic therapy (NAHT versus NACT) was not associated with OS. However, patients with progesterone receptor (PR) positive disease had a 92% lower risk of death compared to patients with PR negative disease. Conclusion: Our data suggest that outcomes are not adversely affected by NAHT in post-menopausal women with ER+ breast cancer. Therefore, NAHT is a viable and potentially less toxic option than NACT in appropriately selected patients. Furthermore, although PR negative disease appears to be associated with poor prognosis, intensification of systemic treatment with chemotherapy may not be associated with improvement of disease-related outcomes in this patient population.